New approaches to the development of information security systems for unmanned vehicles - Bayana B. Ermukhambetova; Grigoriy A. Mun; Sherniyaz B. Kabdushev; Aruzhan B. Kadyrzhan; Kaisarali K. Kadyrzhan; Yelizaveta S. Vitulyova; Ibragim E. Suleimenov (Institute of Advanced Engineering and Science, 2023)
A new approach to ensuring information security is proposed for using in the zone of direct radio visibility. The approach is based on a direct analogy between radio and optical radiation. In the latter case, information protection can be ensured by identifying the point or direction from which the signal comes; all other light sources are cut off by the observer. It is shown that a similar method of information protection can also be implemented in the radio range, which corresponds to modern trends in the development of radio holography. The simplest scheme for detecting the direction to a transmitter, identified as “friend” is presented. Its operability is demonstrated by means of simulation modeling. Ways for the further development of this approach are determined, based on the fact that modern technologies make it possible to implement distributed reception of a radio signal (to use a relatively large number of receivers), which makes it possible to implement direct analogues of such optical elements as a lens, holograms.